DNA barcoding of Stolephorus indicus, Stolephorus commersonnii and Terapon jarbua of Parangipettai Coastal Waters - Khan, S. Ajmal; Lyla, P.S.; John, Akbar; Kumar, C. Prasanna; Murugan, S.; Khan Chowdhury, Ahmed Jalal (Asian Network for Scientific Information, 2010)
Three teleost fishes, Stolephorus indicus, Stolephorus commersonnii and Terapon jarbua occurring in Parangipettai waters, were barcoded (sequenced) for 648 bp region of the mitochondrial cytochrome oxidase subunit I gene (COI) for phylogenetic analysis. All the possible barcode sequences of these three fishes were also extracted via FASTA format from NCBI (National Centre for Biotechnological Information). The genetic distances within the species was small compared to the genetic distances between the species i.e., the genetic distances within S. indicus was 7.67% and the average genetic distance between S. indicus and S. commersonnii was 9.11%. The genetic distance between the families Engraulidae and Terapontidae was 26.48% which was found higher than the genetic distance calculated within the family of Engraulidae (9.11%). This clearly showed that when organisms from distantly placed families are taken, the genetic distance increases. In the present study some phylogeographical signal was apparent in the data. In the neighbor-joining tree for all 10 sequences, two major groups were apparent: clade A comprising of Terapon jarbua and clade B comprising of Stolephorus species. The grouping pattern of clade A showed some phylogeographical signals. The barcode sequence of Lates calcarifer shuffled within other sequences during phylogram constructions was unambiguously placed as an out group in the phylogram. The clades after bootstrapping corresponded well with the expectations. We conclude that precise and accurate identification of Stolephorus indicus, S.commersonnii and Terapon jarbua could be performed using the barcode sequences of the mitochondrial DNA (in the COI gene) of these fishes.